Evaluasi Pemanfaatan Data Penggunaan Jurnal dan E-Book dalam Optimalisasi Sistem Informasi Perpustakaan Universitas Muhammadiyah Ponorogo - Wulandari, Ayu (IQRA`: Jurnal Perpustakaan dan Informasi, 2025)
This study aims to evaluate the utilization of journal and e-book usage data to optimize the library information system at Universitas Muhammadiyah. The main issue in this research is the low integration between electronic resource usage data and decision-making processes in library collection management. A qualitative research method was applied, using data collection techniques such as interviews with library managers and relevant literature studies. The findings reveal that although usage data is available through various platforms (such as ProQuest and EBSCO), it has not been fully utilized to support data-driven decision-making. The results highlight the need for an integrated information system capable of recording, analyzing, and presenting usage data in a structured manner. This research is expected to contribute to the development of more targeted, efficient, and user-oriented digital collection acquisition policies.Keywords: usage data, e-books, electronic journals, library information systems, evaluation